2015
DOI: 10.1007/s11999-015-4157-5
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Advantage to Knotless Barbed Suture in TKA Wound Closure? A Randomized Trial in Simultaneous Bilateral TKAs

Abstract: Background Effective wound closure is critical to minimizing wound complications and withstanding the forces associated with early knee motion after TKA. Barbed sutures allow for knotless fixation, have been used successfully in other specialties, and may provide for more even distribution of tension along the length of the incision; however, data regarding unidirectional barbed sutures from randomized trials have raised important concerns about their use. Bidirectional barbed sutures offer a potential alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
71
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 12 publications
5
71
0
1
Order By: Relevance
“…We did not record the time taken for cystotomy closure since the priority was precise and repeatable closure, not speed. Previous studies measuring the time of suture placement have shown barbed suture is significantly faster to place than conventional suture and we suspect this would translate to cystotomy closure.…”
Section: Discussionmentioning
confidence: 87%
“…We did not record the time taken for cystotomy closure since the priority was precise and repeatable closure, not speed. Previous studies measuring the time of suture placement have shown barbed suture is significantly faster to place than conventional suture and we suspect this would translate to cystotomy closure.…”
Section: Discussionmentioning
confidence: 87%
“…P revious research [1,3,7,9,10] has supported many different wound closure techniques for use in TKA including staples, interrupted sutures, running barbed subcutaneous sutures, and subcuticular methods. A midline incision is generally used, but medial and lateral incisions have also been advocated to permit better kneeling ability after surgery or for other reasons [2,6].…”
mentioning
confidence: 99%
“…There were five premature disengagements and three suture breakages in the CG and none in the BSG. There were no needle stick injuries and no differences in postoperative ROM or outcomes scores [8].…”
Section: Mini Reviewmentioning
confidence: 84%